2012
DOI: 10.1016/j.rmed.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

“Feelings are facts”: Illness perceptions in patients with lung cancer

Abstract: Given the high degree of psychosocial problems in patients with lung cancer, quality medical care would benefit from exploring and addressing and providing potential solutions for these problems. Patients with recently diagnosed non-small-cell lung cancer filled out a questionnaire that assessed illness perceptions and made a drawing of how they perceived their diseased lungs look. They also participated in an interview about the impact of lung cancer in their lives. Scores on the Brief Illness Perception Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 29 publications
2
39
1
1
Order By: Relevance
“…[44] Further, patients with lung cancer are reported to harbor hopes of being cured. [45] For the above reasons, for patients with the most advanced stages of NSCLCs like in this study, suffering pain may arouse doubts about the effectiveness of the medical care for their lung cancer, and reduce the efficacy of the medical care due to a perceived mismatch between their expectations and their physical condition, resulting in the passive-sounding report of the pain. Thus, the pain cluster identified in this study may be unique to the Japanese patients with advanced NSCLCs under standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Further, patients with lung cancer are reported to harbor hopes of being cured. [45] For the above reasons, for patients with the most advanced stages of NSCLCs like in this study, suffering pain may arouse doubts about the effectiveness of the medical care for their lung cancer, and reduce the efficacy of the medical care due to a perceived mismatch between their expectations and their physical condition, resulting in the passive-sounding report of the pain. Thus, the pain cluster identified in this study may be unique to the Japanese patients with advanced NSCLCs under standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This was also reflected in several other illnesses, where analyses of drawings created by participants highlighted the unique ways in which the illnesses or conditions were comprehended and experienced, for example, heart disease,52 menopause,51 postnatal depression53 and human immunodeficiency virus (HIV) infection 40,41. This additional insight emerging through an analysis of patient-created drawings was also observed in studies involving patients with lung cancer,25 severe chronic obstructive pulmonary disease,57 and Ebola infection 35…”
Section: Resultsmentioning
confidence: 79%
“…It would be useful to specify the number and background of raters. Five studies reported the kappa value for inter-observer reliability 25,28,57,59,60. However, kappa statistics can only be useful if the raters are looking at objective elements such as size and quantity of the contents in the drawing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have given good general evidence that depression is a significant problem in lung cancer patients (Lynch et al, 2010;Sharp et al, 2013). And there have been many suggestions of a role for psychological response in the outcome of cancer (Watson et al, 2005;Messina et al, 2010;Knobf, 2011;Hoogerwerf et al, 2012). Despite a large number of patients with lung cancer who receive treatment, there is little published data concerning the psychological responses in the male smokers with lung cancer and its influence on the symptom burden.…”
Section: Introductionmentioning
confidence: 99%